Obesity, mental health, and sexual dysfunction: A critical review - Esfahani, S.; Pal, Sebely (2018)
© The Author(s) 2018. Obesity has profound medical, psychological, and emotional consequences and is associated with sexual difficulties. Little is known regarding the interrelationship between obesity and sexual functioning from a psychological perspective, and less is known regarding treatment options. This review examines these issues and considers various treatments. Literature searches were conducted to locate original research, reviews, systematic reviews, and meta-analyses of obesity, overweight, sexual function, sexual dysfunction, psychological health, mental health, and weight loss. Research demonstrates an association between obesity, mental health, and sexual functioning, but has failed to identify casual pathways between these conditions. Clarifying such pathways is necessary to inform treatment guidelines for clinical practice.